Kohesi Leksikal Dan Kohesi Gramatikal Dalam Bahasa Arab - Muhamad Ichsan Awaludin; Abdullah Nur (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2025)
This study aims to describe cohesion in the Arabic language. The research employs a descriptive qualitative approach, utilizing library research methods. The findings indicate that cohesion in Arabic consists of several types. In this paper, the author presents two main types: lexical cohesion (tamasuk mu‘jami), which includes repetition (tikrār), synonymy (tarāduf), antonymy (taḍādd), hyponymy (ishtimāl), and collocation (muṣāḥabah); and grammatical cohesion (tamasuk naḥwī), which includes substitution, ellipsis, reference, and conjunction. This study is expected to contribute to clarifying the structure of cohesion in Arabic in a systematic and applicable manner, so that it can be utilized in the development of learning materials, such as in tadrībāt lughawiyyah at the intermediate level and similar contexts.